The Relation Between Dialect Density and the Codevelopment of Writing and Reading in African American Children. Issue 4 (15th October 2019) - Puranik, Cynthia; Branum‐Martin, Lee; Washington, Julie A.
Abstract : The purpose of this longitudinal study was to examine the influence of spoken dialect density on writing and on the codevelopment of reading and writing in African American English‐speaking (AAE) children from first through fifth grades. The sample included 869 students, ranging in age from 5.8 to 12.5 years. Results indicated that dialect density had a negative influence concurrently and longitudinally on reading and writing in AAE‐speaking children. High dialect users tended to have weak reading and writing skills and heavier dialect density slowed growth in reading and writing. However, this effect was moderated by the effects of reading and writing on each other. Reading had a facilitative effect on writing even in the presence of heavy dialect use.